Plano Munucipal de saúde: análise do instrumento de gestão - Saliba, Nemre Adas [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Gonçalves, Patricia Elaine; Santos, Joildo Guimarães; Souza, Neila Paula de [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (My University, 2013)
Among planning instruments used by manager instances of Brazilian Health System it pointed the Health Municipal Plan (PMS) that should be built collectively showing political intentions, directresses, priorities, objectives, goals framework, estimative of resources and need costs to get the goals of the health sector. The aim of this work was to analyze the plans in relation to attendance of legal requirements which manage the Brazilian Health System, its constitution and showing of essential items. The study included three municipalities form São Paulo State. It was used the documental analysis as research technique. Near all plans showed an analysis of situation with detailed descriptions of general situation of municipality, and only one of them realized critical analysis of their epidemiological data; the financial income applied on health was decrypted by only one municipality. About programming, all municipalities described the main problems and its solutions. Although they had goals framework, the question about cost estimative to get the goals was not approached. Any municipality showed an annual review, being one of them delayed over than two years. It was observed no participation of Municipal Health Council on elaboration and review of plans. It was concluded that there was a deficiency in the plans analyzed. It’s necessary to execute continuing education with managers in relation to importance of systematic elaboration of plans and to incentive the promotion of active participation of Municipal Health Council promotion of aiming to became true the social control of health actions.

Dentre os instrumentos fundamentais do planejamento que devem ser utilizados pelas instâncias gestoras do Sistema Único de Saúde destaca-se o Plano Municipal de Saúde. Este deve ser construído coletivamente apresentando as intenções políticas, diretrizes, prioridades, objetivos, quadro de metas, estimativa de recursos e gastos necessários para o alcance das metas do setor saúde. O objetivo deste trabalho foi analisar os planos, quanto ao atendimento aos preceitos legais que regem o Sistema Único de Saúde, sua constituição e apresentação dos itens essenciais. Foram incluídos no estudo três municípios do Estado de São Paulo. A técnica de pesquisa adotada foi a análise documental. Verificou-se que nem todos planos apresentaram a análise situacional com descrição detalhada da situação geral do município, e somente um deles realizou análise crítica de seus dados epidemiológicos; assim como, a receita financeira aplicada à saúde foi descrita por apenas um município. Em relação à programação, todos os municípios descreveram os principais problemas e suas soluções. Embora contasse com o quadro de metas, a questão da estimativa de gastos para se atingir as metas não foi abordada. Nenhum apresentou uma revisão anual, estando um deles desatualizado há mais de dois anos. Não foi observada a participação do Conselho Municipal de Saúde na elaboração e revisão dos planos. Concluiu-se que há deficiência nos planos analisados. Sugere-se a execução da educação permanente dos gestores quanto à importância da elaboração sistemática dos planos e da promoção da participação ativa Conselho Municipal de Saúde objetivando concretizar o controle social das ações de saúde.
Health municipal plan: analyse of management’s instrument
Keywords: Policies; Health policy; Health management; Planning; Health planning; Health administration; Políticas; Política de saúde; Gestão em saúde; Planejamento; Planejamento em Saúde; Administração em saúde